3D non-axisymmetric temperature field measurement using rotating tomographic mechanism schlieren method. (3rd September 2021) - Wu, Jun; Li, Yanling; Song, Fengcheng; Zhu, Yuheng; Yu, Zhijing
Abstract: The tomography schlieren method is useful for calculating the non-axisymmetric temperature field, which is relevant to many industrial applications. However, the traditional tomography schlieren method requires bulky imaging devices, which limits its application. Thus, this paper proposes a non-contact three-dimensional temperature field measurement method based on the rotating tomography schlieren method. Projections from different directions of the temperature field are obtained at different angles using a transmission schlieren system, which is controlled by a designed rotating tomographic mechanism. The calibration schlieren method and the projection reconstruction algorithm are used to calculate the 3D temperature field. Verification experiments of single flame and double flame showed that the relative error of the reconstructed temperature was approximately 3.7% compared with a precision thermocouple.